The Role of the Third Acid-Fast Bacillus Smear in Tuberculosis Screening for Infection Control Purposes: A Controversial Topic Revisited - A. Wilmer; E. Bryce; J. Grant (Canadian Journal of Infectious Diseases and Medical Microbiology)
INTRODUCTION: Recent studies have suggested that two negative acid-fast bacillus (AFB) smears may be as effective as three when screening patients with suspected Mycobacterium tuberculosis for respiratory isolation purposes. However, current recommendations in Canada, the United States and Europe still support a three-smear approach.